Aversion to return to work due to fear of COVID19 in the education sector in Tamaulipas - Mexico - Sánchez Limón, Mónica Lorena (2023)
In recent years the world was affected by the COVID 19 pandemic, which forced to change the way in which the economy operated during the contingency, and with it the dynamics of work. The present research has the objective of determining the effects of the fear of COVID 19 on the return to work in the educational sector of Tamaulipa. A sample of 200 workers from the educational sector in the municipalities of Altamira, El Mante, Madero, Reynosa, Tampico, Valle Hermoso and Victoria was collected. The results showed that there is a negative relationship between fear of COVID 19 and return to work. It is concluded that fear was the main factor that generated aversion to returning to work in the educational sector of Tamaulipas, accompanied by the physical consequences of the disease and major problems such as psychological disorders. This negatively affected the return to work spaces.